Diarrheagenic Escherichia coli and Acute and Persistent Diarrhea in Returned Travelers - Schultsz, C. (American Society for Microbiology, 2000)
To determine the role of diarrheagenic Escherichia coli in acute and persistent diarrhea in returned travelers, a case control study was performed. Enterotoxigenic E. coli (ETEC) was detected in stool samples from 18 (10.7%) of 169 patients and 4 (3.7%) of 108 controls. Enteroaggregative E. coli (EAggEC) was detected in 16 (9.5%) patients and 7 (6.5%) controls. Diffuse adherent E. coli strains were commonly present in both patients (13%) and controls (13.9). Campylobacter and Shigella species were the other bacterial enteropathogens most commonly isolated (10% of patients, 2% of controls). Multivariate analysis showed that the presence of ETEC was associated with acute diarrhea (odds ratio [OR], 6.7; 95% confidence interval [CI], 1.5 to 29.1; P = 0.005), but not with persistent diarrhea (OR, 1.6; 95% CI, 0.4 to 7.4). EAggEC was significantly more often present in patients with acute diarrhea than in controls (P = 0.009), but no significant association remained after multivariate analysis. ETEC and EAggEC are frequently detected in returned travelers with diarrhea. The presence of ETEC strains is associated with acute but not with persistent diarrhea.